Control of cell proliferation by a porous chitosan scaffold with multiple releasing capabilities - Cai, Shu-Jyun; Li, Ching-Wen; Weihs, Daphne; Wang, Gou-Jen (Science and technology of advanced materials, 2017)
The aim of this study was to develop a porous chitosan scaffold with long-acting drug release as an artificial dressing to promote skin wound healing. The dressing was fabricated by pre-freezing at different temperatures (−20 and −80 °C) for different periods of time, followed by freeze-drying to form porous chitosan scaffolds with different pore sizes. The chitosan scaffolds were then used to investigate the effect of the controlled release of fibroblast growth factor-basic (bFGF) and transforming growth factor-β1 (TGFβ1) on mouse fibroblast cells (L929) and bovine carotid endothelial cells (BEC). The biocompatibility of the prepared chitosan scaffold was confirmed with WST-1 proliferation and viability assay, which demonstrated that the material is suitable for cell growth. The results of this study show that the pore sizes of the porous scaffolds prepared by freeze-drying can change depending on the pre-freezing temperature and time via the formation of ice crystals. In this study, the scaffolds with the largest pore size were found to be 153 ± 32 μm and scaffolds with the smallest pores to be 34 ± 9 μm. Through cell culture analysis, it was found that the concentration that increased proliferation of L929 cells for bFGF was 0.005 to 0.1 ng/mL, and the concentration for TGFβ1 was 0.005 to 1 ng/mL. The cell culture of the chitosan scaffold and growth factors shows that 3.75 ng of bFGF in scaffolds with pore sizes of 153 ± 32 μm can promote L929 cell proliferation, while 400 pg of TGFβ1 in scaffolds with pore size of 34 ± 9 μm can enhance the proliferation of L929 cells, but also inhibit BEC proliferation. It is proposed that the prepared chitosan scaffolds can form a multi-drug (bFGF and TGFβ1) release dressing that has the ability to control wound healing via regulating the proliferation of different cell types.